Mechanism of insulin resistance in a rat model of kidney disease and the risk of developing type 2 diabetes. - François Dion; Christopher Dumayne; Nathalie Henley; Stéphanie Beauchemin; Edward B Arias; François A Leblond; Sylvie Lesage; Stéphane Lefrançois; Gregory D Cartee; Vincent Pichette (PLoS ONE, 2017)
Chronic kidney disease is associated with homeostatic imbalances such as insulin resistance. However, the underlying mechanisms leading to these imbalances and whether they promote the development of type 2 diabetes is unknown. The effect of chronic kidney disease on insulin resistance was studied on two different rat strains. First, in a 5/6th nephrectomised Sprague-Dawley rat model of chronic kidney disease, we observed a correlation between the severity of chronic kidney disease and hyperglycemia as evaluated by serum fructosamine levels (p<0.0001). Further, glucose tolerance tests indicated an increase of 25% in glycemia in chronic kidney disease rats (p<0.0001) as compared to controls whereas insulin levels remained unchanged. We also observed modulation of glucose transporters expression in several tissues such as the liver (decrease of ≈40%, p≤0.01) and muscles (decrease of ≈29%, p≤0.05). Despite a significant reduction of ≈37% in insulin-dependent glucose uptake in the muscles of chronic kidney disease rats (p<0.0001), the development of type 2 diabetes was never observed. Second, in a rat model of metabolic syndrome (Zucker Leprfa/fa), chronic kidney disease caused a 50% increased fasting hyperglycemia (p<0.0001) and an exacerbated glycemic response (p<0.0001) during glucose challenge. Similar modulations of glucose transporters expression and glucose uptake were observed in the two models. However, 30% (p<0.05) of chronic kidney disease Zucker rats developed characteristics of type 2 diabetes. Thus, our results suggest that downregulation of GLUT4 in skeletal muscle may be associated with insulin resistance in chronic kidney disease and could lead to type 2 diabetes in predisposed animals.